2019
DOI: 10.1088/1361-6463/ab1a02
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low temperature atmospheric nitrogen plasma on MC3T3-E1 preosteoblast proliferation and differentiation in vitro

Abstract: The aim of this work was to evaluate the impact of atmospheric pressure nitrogen plasma on viability, proliferation, and osteogenic differentiation of normal mouse calvarial preosteoblasts (MC3T3-E1 Subclone 4), which were maintained in Hanks’ balanced salt solution (HBSS) during plasma exposure. Obtained results clearly demonstrated that short-time (4, 8, and 16 s) nitrogen plasma treatment is non-toxic to the MC3T3-E1 cells, does not affect cell morphology, promotes preosteoblasts’ proliferation, enhances os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…Furthermore, cells revealed higher viability after 16 s exposure to nitrogen plasma compared to the air plasma. In our another study [ 15 ], it was demonstrated that 16 s nitrogen plasma treatment promoted preosteoblasts proliferation and enhanced their osteogenic differentiation. Importantly, the best results were obtained when MC3T3-E1 preosteoblasts were left in Hanks’ Balanced Salt solution (HBSS) for 3 h after plasma exposure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, cells revealed higher viability after 16 s exposure to nitrogen plasma compared to the air plasma. In our another study [ 15 ], it was demonstrated that 16 s nitrogen plasma treatment promoted preosteoblasts proliferation and enhanced their osteogenic differentiation. Importantly, the best results were obtained when MC3T3-E1 preosteoblasts were left in Hanks’ Balanced Salt solution (HBSS) for 3 h after plasma exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Stem cells-seeded biomaterials were exposed to cold nitrogen plasma for 16 s and left for 3 h in HBSS after plasma treatment. These conditions were demonstrated in our previous studies to be very effective in stimulation of proliferation and ECM synthesis by MC3T3-E1 preosteoblasts [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations